Pilot study of a novel vacuum-assisted method for decellularization of tracheae for clinical tissue engineering applications - Lange, P.; Greco, K.; Partington, L.; Carvalho, C.; Oliani, S. [UNESP]; Birchall, M. A.; Sibbons, P. D.; Lowdell, M. W.; Ansari, T. (Hindawi, 2017)
Tissue engineered tracheae have been successfully implanted to treat a small number of patients on compassionate grounds. The treatment has not become mainstream due to the time taken to produce the scaffold and the resultant financial costs. We have developed a method for decellularization (DC) based on vacuum technology, which when combined with an enzyme/detergent protocol significantly reduces the time required to create clinically suitable scaffolds. We have applied this technology to prepare porcine tracheal scaffolds and compared the results to scaffolds produced under normal atmospheric pressures. The principal outcome measures were the reduction in time (9 days to prepare the scaffold) followed by a reduction in residual DNA levels (DC no-vac: 137.8±48.82 ng/mg vs. DC vac 36.83±18.45 ng/mg, p<0.05.). Our approach did not impact on the collagen or glycosaminoglycan content or on the biomechanical properties of the scaffolds. We applied the vacuum technology to human tracheae, which, when implanted in vivo showed no significant adverse immunological response. The addition of a vacuum to a conventional decellularization protocol significantly reduces production time, whilst providing a suitable scaffold. This increases clinical utility and lowers production costs. To our knowledge this is the first time that vacuum assisted decellularization has been explored. Copyright © 2015 John Wiley & Sons, Ltd.
Keywords: decellularization; tissue engineering; trachea; transplantation; vacuum